2005
DOI: 10.4067/s0034-98872005000500006
|View full text |Cite
|
Sign up to set email alerts
|

Malformaciones congénitas en hijos de madres con diabetes gestacional

Abstract: Pregnant women with pre-existing or gestational diabetes have a higher risk of giving birth a child with malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
1
3
0
3
Order By: Relevance
“…The result of the present study found that mothers with diabetes Mellitus were 9 times at greater risk of having children with congenital malformations. This in line with the study done in University of Chile Clinical Hospital reporting gestational diabetes associated with CM [25]. Hence, more attention should be taken to the control of diabetes especially during the first trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…The result of the present study found that mothers with diabetes Mellitus were 9 times at greater risk of having children with congenital malformations. This in line with the study done in University of Chile Clinical Hospital reporting gestational diabetes associated with CM [25]. Hence, more attention should be taken to the control of diabetes especially during the first trimester of pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Em uma revisão da literatura sobre a mortalidade perinatal no Brasil, destacase que a maioria dos óbitos é considerada evitável, e as principais falhas apontadas se encontram na qualidade da assistência ao pré-natal, ao parto e à assistência neonatal 28 . Além das complicações na mulher, o diabetes gestacional e a pré-eclâmpsia são doenças relacionadas à máformação congênita, aos problemas respiratórios no concepto e ao crescimento intra-uterino restrito, por exemplo 29,30 . Nesse sentido, destacase a importância do controle das morbidades maternas com a realização de um pré-natal de qualidade.…”
Section: Or Bruta (Ic90%)unclassified
“…Periconceptional folic acid supplementation has been shown to reduce significantly the first occurrence and recurrence of neural tube defects (NTDs) in humans, pointing to its role in the pathogenesis of this condition. However, in experimental animals, a variety of environmental agents have been implicated, including ethanol (10,28) , inhibition of cholesterol synthesis (6,10) , retinoic acid (45) , vitamin A (23) , hyperglycemia (12,43) , hypoxia (2,13) , ionizing radiation/ hyperthermia (30) and nicotine (18,24) .…”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that babies born to diabetic mothers are 3 to 4 times more prone to present congenital anomalies than is the general population (21,34) . Such anomalies have been correlated with inefficient blood glucose control (34,43) which may induce diabetic embryopathy, which encompasses NTDs and other system defects (12,16) .…”
Section: Introductionmentioning
confidence: 99%